LANGSA COMMUNITY LEGAL AWARENESS AND COMPLIANCE AGAINST QANUN PRAYER IN CONGREGATION - Zulfikar Zulfikar; Jaidatul Fikri; Sitti Suryani (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2021)
This paper aims to find out how awareness ang legal compliance of the people in Langsa city regarding congregational prayer. This research is a field research, using qualitative methods with a normative approach and legal sociology. Data collection was carried out by observation, interviews and documentation. The results showed that some people have a high awareness of the obligation to pray in congregation, namely internalization, but others still have low levels of awareness and compliance with the law. The conscious and obedient behavior of the people in Langsa city regarding the implementation of congregational prayer is conscious behavior and obedience to religious orders, not obedience to qanun number 11 of 2002